Gestational diabetes mellitus: Impacts on fetal neurodevelopment, gut dysbiosis, and the promise of precision medicine - Biete, Michelle; Vasudevan, Sona (Frontiers in Molecular Biosciences, 2024)
Gestational Diabetes Mellitus (GDM) is a common metabolic disorder affecting about 16.5% of pregnancies worldwide and causes significant health concerns. GDM is a serious pregnancy complication caused by chronic insulin resistance in the mother and has been associated with the development of neurodevelopmental disorders in offspring. Emerging data support the notion that GDM affects both the maternal and fetal microbiome, altering the composition and function of the gut microbiota resulting in dysbiosis. The observed dysregulation of microbial presence in GDM pregnancies has been connected to fetal neurodevelopmental problems. Several reviews have focused on the intricate development of maternal dysbiosis affecting the fetal microbiome. Omics data have been instrumental in deciphering the underlying relationship between GDM, gut dysbiosis, and fetal neurodevelopment, paving the way for precision medicine. Microbiomeassociated omics analyses help elucidate how dysbiosis contributes to metabolic disturbances and inflammation, linking microbial changes to adverse pregnancy outcomes such as those seen in GDM.Integrating omics data across these different layers-genomics, transcriptomics, proteomics, metabolomics, and microbiomics-offers a comprehensive view of the molecular landscape underlying GDM. This review outlines the affected pathways and proposes future developments and possible Biete et. al 2 personalized therapeutic interventions by integrating omics data on maternal microbiome, genetics, lifestyle factors, and other relevant biomarkers aimed at identifying women at high risk of developing GDM. For example, Machine Learning tools have emerged with powerful capabilities to extract meaningful insights from large datasets.